2021
DOI: 10.11646/zootaxa.4915.3.10
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Loricaria (Siluriformes: Loricariidae) from the Turiaçu River basin, Eastern Amazon region, Brazil

Abstract: A new species of Loricaria is herein described from the Turiaçu River basin, Eastern Amazon region, Maranhão state, Brazil, within the Maranhão Hydrological Unit (MHU). Loricaria turi differs from its congeners mainly by the following combination of characters: abdominal plate development confined to the posterior median region, pectoral girdle mostly naked, with cluster of plates near pectoral fin bases; large eyes (minimum orbital diameter 16.2–20.7% of HL and maximum orbital diameter 19.8–24.0% of HL), 214.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 839 publications
(2 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…The specimens were first fixed in 10% formalin for a few days and then transferred to 70% alcohol for permanent storage (Malabarba and Reis, 1987). The specimens were identified using specialized references for each taxonomic group (Malabarba, 2004;Buitrago-Suárez and Burr, 2007;Piorski et al, 2008;Birindelli et al, 2011;Ottoni, 2011;Ribeiro et al, 2017;Guimarães et al, 2018;Saraiva et al, 2021;Oliveira et al, 2022), and were later confirmed by one of the authors of the present study (José Luís Olivan Birindelli), a specialist in fish taxonomy. The voucher material was deposited in the ichthyological collection of the Museum of Zoology at Londrina State University (MZUEL).…”
Section: Collection and Identification Of The Specimensmentioning
confidence: 73%
See 1 more Smart Citation
“…The specimens were first fixed in 10% formalin for a few days and then transferred to 70% alcohol for permanent storage (Malabarba and Reis, 1987). The specimens were identified using specialized references for each taxonomic group (Malabarba, 2004;Buitrago-Suárez and Burr, 2007;Piorski et al, 2008;Birindelli et al, 2011;Ottoni, 2011;Ribeiro et al, 2017;Guimarães et al, 2018;Saraiva et al, 2021;Oliveira et al, 2022), and were later confirmed by one of the authors of the present study (José Luís Olivan Birindelli), a specialist in fish taxonomy. The voucher material was deposited in the ichthyological collection of the Museum of Zoology at Londrina State University (MZUEL).…”
Section: Collection and Identification Of The Specimensmentioning
confidence: 73%
“…The fish fauna of the Brazilian state of Maranhão has been the subject of a number of different studies over the past few decades, which have made advances in the areas of taxonomy, the systematics of both species and groups, including the description of new taxa, the composition of communities, geographic distributions, and biogeography (Piorski et al, 1998(Piorski et al, , 2003(Piorski et al, , 2008(Piorski et al, , 2017Soares, 2005;Castro et al, 2010;Barros et al, 2011;Birindelli et al, 2011;Castro and Dourado, 2011;Ottoni, 2011;Fraga et al, 2012;Almeida et al, 2013;Ramos et al, 2014;Ribeiro et al, 2014;Lima et al, 2015Lima et al, , 2019Matavelli et al, 2015;Melo et al, 2016;Nascimento et al, 2016;Guimarães et al, 2018Guimarães et al, , 2020aGuimarães et al, , b, c, 2021Abreu et al, 2019;Almeida et al, 2019;Brito et al, 2019;Teixeira et al, 2019;Oliveira et al, 2020Oliveira et al, , 2022Saraiva et al, 2021;Silva et al, 2021;Dutra et al, 2022;Vieira et al, 2023). Based on a review of the published hydrographic basins of the Mearim and Pindaré rivers, as well as the secondary basins of the Aurá, Pericumã, and Turiaçu rivers, which overflow and inundate the local floodplains on an annual cycle, forming a large number of both temporary and permanent lakes (Almeida-Funo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%